2008
DOI: 10.1152/ajprenal.00036.2008
|View full text |Cite
|
Sign up to set email alerts
|

Role of AQP1 in endotoxemia-induced acute kidney injury

Abstract: The effect of endotoxemia (lipopolysaccharide, 2.5 mg/kg ip) was investigated in aquaporin (AQP) 1 knockout (KO) compared with wild-type (WT) mice. At baseline, KO mice exhibited higher water intake (WI) and urine output (UO). After endotoxemia, WI and UO remained higher in the KO than WT mice, and urine osmolality was lower. The higher serum osmolality in AQP1-KO mice during endotoxemia was associated with higher AQP2 (133 +/- 8 vs. 100 +/- 3%, P < 0.01), AQP3 (140 +/- 8 vs. 100 +/- 4%, P < 0.001) and Na(+)-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 17 publications
2
50
0
Order By: Relevance
“…GFR reduction by inflammatory stimuli has been reported previously (19)(20)(21). In clinical trials, GFR reduction was reported during inflammation especially when blood flow and/or blood pressure were substantially reduced, for example, in hypodynamic septic shock associated with a lowered cardiac output, which leads to a significant reduction in the clearance of a variety of drugs (34).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…GFR reduction by inflammatory stimuli has been reported previously (19)(20)(21). In clinical trials, GFR reduction was reported during inflammation especially when blood flow and/or blood pressure were substantially reduced, for example, in hypodynamic septic shock associated with a lowered cardiac output, which leads to a significant reduction in the clearance of a variety of drugs (34).…”
Section: Discussionmentioning
confidence: 76%
“…Administration of LPS is known to induce significant reductions in the GFR and tubular function, as commonly observed in patients with septic shock (18)(19)(20)(21). It has also been reported that LPS treatment downregulates OAT transcripts and protein expression in the kidneys and upregulates PEPT2 transcripts in the choroid plexus (7,22).…”
mentioning
confidence: 91%
“…AQP1 expression in the kidney could have a protective role in LPS induced endotoxemia (presence of LPS in the blood stream). Knock-out mice lacking AQP1 show a predisposition to endotoxemia-induced acute kidney injury [134]. Taken together, these data are adding pieces to the puzzle of emerging data for a role of AQPs and especially AQP9 in the immune response to bacterial infections.…”
Section: Lipopolysaccharide and Aquaporinsmentioning
confidence: 80%
“…For assessment of injury, 5-mm kidney sections were stained with periodic acid-Schiff. Acute tubular necrosis was determined in the outer stripe of the outer medulla and cortex using a semiquantitative scale in which the percentage of tubules showing epithelial necrosis, brush-border loss, and cast formation was assigned a score: 0 = normal, 1 = ,10%, 2 = 11-25%, 3 = 26-45%, 4 = 46-75%, and 5 = .76% (26,27).…”
Section: Histologymentioning
confidence: 99%